Do Macroeconomic Factors Impact Corporate Debt? Evidence from India - Faniband, Muhammadriyaj; Marulkar , Kedar (Asian Journal of Empirical Research, 2020)
We study the impact of macroeconomic factors on corporate debt in India during April 2000 to March 2018 period using quantile regression. Our quantile regression outcomes reveal that the impact of consumer price index on corporate debt is significant and positive across the quantiles. However, the wholesale price index has a significant and negative impact on debt level. Interest rate and exchange rate do not show similar impact across the quantiles. In this paper, the results of quantile regression are also compared with ordinary least squares regression. The results of ordinary least squares regression indicate that all macroeconomic factors under study affect the corporate debt level.